2018
DOI: 10.1124/dmd.118.081042
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Xenobiotic Receptors: Beyond Chemical Disposition

Abstract: Over the past 20 years, the ability of the xenobiotic receptors to coordinate an array of drug-metabolizing enzymes and transporters in response to endogenous and exogenous stimuli has been extensively characterized and well documented. The constitutive androstane receptor (CAR) and the pregnane X receptor (PXR) are the xenobiotic receptors that have received the most attention since they regulate the expression of numerous proteins important to drug metabolism and clearance and formulate a central defensive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 175 publications
(204 reference statements)
0
95
0
Order By: Relevance
“…This is due to a number of confounding factors that affect oral drug absorption including the properties of the compound (solubility, permeability), physiology of the intestinal tract (transit time, blood flow), and patient phenotype (including age, gender, polymorphism in drug metabolizing enzymes, disease states) 5 . Species differences in the isoforms, regional abundances, differences in substrate specificity of drug metabolism enzymes [6][7][8] and transporters 9,10 , and mechanism regulating transcriptional activation 11,12 , precludes accurate extrapolation of the data from animal models to the clinic. In mice, for example, there are 34 cytochromes CY450 in the major gene families involved in drug metabolism, i.e., the Cyp1a, Cyp2c, Cyp2d, and Cyp3a gene clusters, while in humans, there are only eight 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to a number of confounding factors that affect oral drug absorption including the properties of the compound (solubility, permeability), physiology of the intestinal tract (transit time, blood flow), and patient phenotype (including age, gender, polymorphism in drug metabolizing enzymes, disease states) 5 . Species differences in the isoforms, regional abundances, differences in substrate specificity of drug metabolism enzymes [6][7][8] and transporters 9,10 , and mechanism regulating transcriptional activation 11,12 , precludes accurate extrapolation of the data from animal models to the clinic. In mice, for example, there are 34 cytochromes CY450 in the major gene families involved in drug metabolism, i.e., the Cyp1a, Cyp2c, Cyp2d, and Cyp3a gene clusters, while in humans, there are only eight 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the expression levels of many of the major human CYP450 enzymes and drug transporter (which determine levels and variability in drug exposure) are controlled by multiple transcription factors, primarily the xenosensors constitutive androstane receptor (CAR), pregnane X receptor (PXR), and aryl hydrocarbon receptor (AhR). These nuclear receptors also exhibit marked species differences in their activation by drugs and exogenous chemicals 11 . For example, rifampicin and SR12813 are potent agonists for human PXR (hPXR) but not for mouse PXR (mPXR), whereas the potent mPXR agonist 5-pregnen-3β-ol-20-one-16α-carbonitrile (PCN) is a poor agonist for hPXR 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Upon activation, PXR and CAR play critical roles in xenobiotic bioactivation and detoxification (Handschin and Meyer, 2003). In addition, recent studies have unveiled novel functions of these drug receptors in various intermediary metabolism pathways, such as lipid and glucose metabolism (Poulin-Dubois and Shultz, 1990;Wada et al, 2009;Gao and Xie, 2010;Mackowiak et al, 2018;Pu et al, 2018). Our research group and others have extensively characterized the effect of pharmacologic activation of PXR and CAR on the regulation of various protein-coding genes, especially the drugprocessing genes in liver (Cheng et al, 2005b;Maher et al, 2005;Kiyosawa et al, 2008;Pratt-Hyatt et al, 2013;Oshida et al, 2015;Cui and Klaassen, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, a balance between PXR transcriptional activation and repression is needed, not only to maintain appropriate physiologic levels of endogenous chemicals but also to achieve optimal therapeutic efficacy with fewer drug‐induced toxicities. Because of its important role in regulating drug efficacy and drug toxicity, as well as its emerging roles in other physiologic and pathologic processes such as energy metabolism and metabolic diseases, infectious diseases, cancer, and inflammatory bowel disease (IBD), as briefly discussed in Sections to , PXR has become an attractive therapeutic target . However, PXR is notorious for promiscuously binding structurally diverse chemicals, including clinical drugs, environmental toxins, and endogenous metabolites, making it a challenging therapeutic target partly because of the perceived difficulty of studying its structure‐activity relationship .…”
Section: Introductionmentioning
confidence: 99%
“…The review is heavily oriented toward molecular mechanisms derived from reported structural information. The justification for the discovery of such PXR modulators is presented in context with the important function of PXR in drug metabolism and human disease, complementing recent perspectives on the field …”
Section: Introductionmentioning
confidence: 99%